CLADISTIC ANALYSIS OF THE MIDDLE JURASSIC AMMONITE RADIATION - Moyne S.; Neige P. (My University, 2004)
Cladistic analysis of the Middle Jurassic ammonite radiation shows how the Aalenian-age ancestral stock, known variously as the Hammatocerataceae or Hammatoceratinae, gave rise to numerous new groups in Bajocian times. Cladistic analysis shows this ancestral stock is not a single lineage but two: the 'Erycites group', which gave rise to the Stephanocerataceae, and the 'Hammatoceras group', from which all other Bajocian groups derived.
Keywords: PHYLOGENY; CLADISTICS; AMMONOIDS; JURASSIC; Mesozoic::Jurassic; Мезозой::Юрская